SAT0046 Intra-articular CD1C-expressing myeloid dendritic cells from RA patients express increased levels of T cell-attracting chemokines and induce TH1, TH2, and TH17 cell activity. (23rd January 2014) - Moret, F.M.; Hack, C.E.; van der Wurff-Jacobs, K.M.; Bijlsma, J.W.; Lafeber, F.P.; van Roon, J.A.
Abstract : Background: Myeloid dendritic cells (mDCs) are potent T cell-activating antigen-presenting cells that have been implicated to play a crucial role in the regulation of tolerance and pro-inflammatory immune responses in many disease states, including rheumatoid arthritis (RA). Despite this, studies that have reported on the role of naturally occurring circulating mDCs in RA are scarce. Recently, CD1c+ mDCs from RA patients were suggested to migrate from the circulation to the joint where they exhibit a semi-mature phenotype. However, data on the capacity of these CD1c+ mDCs to regulate T cell activation in RA are lacking. Objectives: To study the unique expression profiles of co-stimulatory molecules and pro-inflammatory mediators secreted by CD1c+ mDCs from synovial fluid (SF) as compared to peripheral blood (PB) of RA patients and to investigate their capacity to stimulate proliferation and cytokine production of autologous CD4 T cells. Methods: CD1c+ mDC numbers and their expression of surface molecules involved in T cell activation were assessed by FACS analysis in SF and PB from RA patients (n=9). Production of inflammatory mediators by CD1c+ mDCs from SF and PB of RA patients (n=6) was determined after 20h of culture by multiplex immunoassay (measuring 51 cytokines). The capacity of CD1c+ mDCs from SF (n=5) and PB (n=11) to activate autologous CD4 T cell proliferation in the absence of additional stimuli was measured after 6 days of culture by 3 H-thymidine incorporation assay. Additionally, T-cell cytokine production was measured upon ionomycin/PMA restimulation. Results: The number of CD1c+ mDCs was significantly increased in SF versus PB of RA patients (mean 5.0% vs. 0.6%, resp., p<0.01). mDCs from SF showed increased expression of CD80 and CD86 (CD80: MFI 131 vs. 68, p<0.04; CD86: 157 vs. 89, p<0.02, resp.). Additionally, the number of positive mDCs for HLA-II, CD80 and CD40 was significantly increased in SF versus PB (all p<0.05). Numerous cytokines were abundantly and equally produced by mDCs both from PB and SF (incl. IL-12, IL-23, IL-13, IL-21). mDCs from SF produced higher IP10, MIG, TARC, and OPG concentrations as compared to mDCs from PB (IP10: 247 vs. 54, p<0.05; MIG: 90 vs. 24, p<0.01; TARC: 26 vs. 1, p<0.01; OPG: 354 vs. 156, p<0.05, resp., all pg/ml). By contrast, MDC secretion by mDCs from SF was significantly lower than mDCs from PB (2456 vs. 4397 pg/ml, p<0.05, resp.). mDCs from SF had a strongly increased capacity to induce proliferation of CD4 T cells as compared to mDCs from PB (ratio DC:T cell 1:5, 26935 vs. 1503 CPM, p<0.01, resp.). The augmented T cell proliferation was associated with a strongly increased IFNγ, IL-17, and IL-4 cytokine production (ratio DC:T cell 1:5, SF vs. PB, IFNγ: 3428 vs. 179 pg/ml; IL-17: 363 vs. 39 pg/ml; IL-4: 193 vs. 17 pg/ml, resp.). Conclusions: The present study indicates that increased numbers of CD1c+ mDCs in SF play an essential role in the inflammation cascade by the secretion of specific T cell-attracting chemokines and the activation of self-reactive T cells to induce Th1, Th2, and Th17 activity. Targeting of CD1c+ mDCs or specific triggers of these cells could be beneficial to prevent immunopathology of RA. Disclosure of Interest: None Declared